Traditional and modern cartographic materials for geography teaching: From Blaž Kocen to the present - Bratec Mrvar, Rožle; Gašperič, Primož (Acta geographica Slovenica, 2023)
This article presents cartographic teaching materials used in two different periods: the second half of the nineteenth century and the beginning of the 2020s. During the first period examined, the works of Blaž Kocen (also Blasius Kozenn) laid the foundations of school cartography in the Habsburg Monarchy. The most highly valued among them in central Europe were his atlases, which have the longest tradition of publishing in the world. In the second period, technological development and the COVID-19 pandemic laid the foundations for a faster transition to digital approaches to teaching. This article examines the use of maps, atlases, and textbooks by Slovenian geography teachers to determine whether modern (digital) teaching materials have replaced or will replace the traditional (paper) ones. It was established that the use of printed cartographic materials continues to predominate in geography teaching, which indirectly preserves the importance of Kocen’s pioneering and visionary work.